2019
DOI: 10.1158/1078-0432.ccr-18-1593
|View full text |Cite
|
Sign up to set email alerts
|

Low-pass Whole-genome Sequencing of Circulating Cell-free DNA Demonstrates Dynamic Changes in Genomic Copy Number in a Squamous Lung Cancer Clinical Cohort

Abstract: Purpose: We developed a method to monitor copy number variations (CNV) in plasma cell-free DNA (cfDNA) from patients with metastatic squamous non-small cell lung cancer (NSCLC). We aimed to explore the association between tumor-derived cfDNA and clinical outcomes, and sought CNVs that may suggest potential resistance mechanisms. Experimental Design: Sensitivity and specificity of low-pass whole-genome sequencing (LP-WGS) were first determined using cell line DNA and cfDNA. LP-WGS was performed on baseline and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 50 publications
(58 reference statements)
9
81
0
Order By: Relevance
“…This led to the phase II FIGARO study of pictilisib in combination with first-line chemotherapy; however, preliminary data did not reveal any significant progressionfree survival (PFS) or overall survival (OS) benefit. 84 Similar findings have been reported in a phase IA/IB trial in a Japanese cohort of patients. 85 PX-866 has been evaluated in combination with docetaxel chemotherapy in a randomized phase II trial of advanced, refractory NSCLC patients.…”
Section: Clinical Trials Of Pi3k/akt/mtor Inhibitors In Nsclcsupporting
confidence: 81%
See 1 more Smart Citation
“…This led to the phase II FIGARO study of pictilisib in combination with first-line chemotherapy; however, preliminary data did not reveal any significant progressionfree survival (PFS) or overall survival (OS) benefit. 84 Similar findings have been reported in a phase IA/IB trial in a Japanese cohort of patients. 85 PX-866 has been evaluated in combination with docetaxel chemotherapy in a randomized phase II trial of advanced, refractory NSCLC patients.…”
Section: Clinical Trials Of Pi3k/akt/mtor Inhibitors In Nsclcsupporting
confidence: 81%
“…Of 66 patients, 29 (43.9%) had partial response and 20 (30.9%) had stable disease. This led to the phase II FIGARO study of pictilisib in combination with first‐line chemotherapy; however, preliminary data did not reveal any significant progression‐free survival (PFS) or overall survival (OS) benefit . Similar findings have been reported in a phase IA/IB trial in a Japanese cohort of patients .…”
Section: Clinical Trials Of Pi3k/akt/mtor Inhibitors In Nsclcmentioning
confidence: 65%
“…Shallow genome-wide sequencing provides a way for estimation of tumor burden [20]. Several studies adopted this approach in breast cancer, lung cancer, prostate carcinoma, and neuroblastoma and found the estimated tumor fractions are clinically relevant [33][34][35][36][37][38]. We found that TFx was remarkably higher in the metastatic setting than localized tumor.…”
Section: Discussionmentioning
confidence: 75%
“…Detecting CNAs in cfDNA is challenging, and depends also on the level of amplification of the gene in the tumor which in turns, involves deeper sequencing 56 . In humans, more reliable methods are used to detect CNA in cfDNA like low-pass whole genome sequencing 57 . Beck et al used whole genome sequencing on tumor and plasma samples of 2 dogs with mammary carcinoma and found a good concordance of tumor and cfDNA copy number profiles for the regions with high-level amplifications 50 .…”
Section: Discussionmentioning
confidence: 99%